2021
DOI: 10.1503/cmaj.202756
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for outbreaks of SARS-CoV-2 infection at retirement homes in Ontario, Canada: a population-level cohort study

Abstract: BACKGROUND:The epidemiology of SARS-CoV-2 infection in retirement homes (also known as assisted living facilities) is largely unknown. We examined the association between homeand community-level characteristics and the risk of outbreaks of SARS-CoV-2 infection in retirement homes since the beginning of the first wave of the COVID-19 pandemic. METHODS:We conducted a populationbased, retrospective cohort study of licensed retirement homes in Ontario, Canada, from Mar. 1 to Dec. 18, 2020. Our primary outcome was … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 21 publications
5
20
0
Order By: Relevance
“…Our results indicate that there is a complex interplay between the risk of SARS-CoV-2 infection and subsequent clinical outcome, mediated by individual level factors (age, gender, and chronic conditions) and contextual factors. Particularly, size of residence and community incidence showed the highest influence on infection acquisition, as has been observed previously [ 6 , 22 ], with high OR (3.18 and 2.28, respectively). This may be explained because large nursing homes were more susceptible to a SARS-CoV-2 carrier entering the premises due to the higher number of visiting relatives and working staff.…”
Section: Discussionsupporting
confidence: 80%
“…Our results indicate that there is a complex interplay between the risk of SARS-CoV-2 infection and subsequent clinical outcome, mediated by individual level factors (age, gender, and chronic conditions) and contextual factors. Particularly, size of residence and community incidence showed the highest influence on infection acquisition, as has been observed previously [ 6 , 22 ], with high OR (3.18 and 2.28, respectively). This may be explained because large nursing homes were more susceptible to a SARS-CoV-2 carrier entering the premises due to the higher number of visiting relatives and working staff.…”
Section: Discussionsupporting
confidence: 80%
“…Additional research is needed to disentangle deaths directly attributable to COVID-19 vs those that may have occurred owing to other causes. We note and retirement home 36 sectors globally owing to challenges in infection control, issues with staffing and staff transmission, 37,38 and limitations placed on family and friends entering facilities. 39 While the present study's mortality findings in those with dementia likely highlight the outcomes of COVID-19 in the retirement home setting, individuals with dementia may have also had a higher mortality risk during the pandemic associated with decreased access to community support and hospital care.…”
Section: Discussionmentioning
confidence: 99%
“…In Canada, governmentrun LTCHs had lower mortality than for-profit LTCHs [4,5]. For-profit LTCHs had the following organisational factors that are associated with higher numbers of COVID-19 deaths among residents: they were more often crowded, and their staff were more often underpaid, less likely to secure full-time positions, often employed at more than one center, or employed on casual terms with fewer benefits when compared with staff at nonprofit private or public homes [6][7][8][9]. Further studies conducted in Australia, England, and Spain confirmed that larger homes experienced higher mortality rates; however, the findings on the impact of ownership and administration type were inconsistent.…”
Section: Introductionmentioning
confidence: 99%